PENDIDIKAN LITERASI KEUANGAN MELALUI PROGRAM KEMITRAAN DENGAN BANK UNTUK MENGURANGI PERILAKU KONSUMTIF PADA MAHASISWA - Dhany Efita Sari (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2018)
The stability of the financial sector of a country can be determined by the rate of people’s financial literacy in financial product which is should be no lower than 30% of people have good knowledge in financial products. The results of survey conducted by the financial service authority of Indonesia (OJK) in 2006 indicated that the Indonesian literacy is still very low (21.8%). People who have good financial literacy are able to arrange wisely their family and own financial. In fact, the young generation especially university students of accounting education in Universitas Muhammadiyah Surakarta are wasteful, following the current trend, and unaware of saving. The research aims to describe the implementation of literacy education for accounting education students in UMS through bank partnership to lessen consumptive behavior. This research was a literature study by using qualitative approach. The research found the wasteful behavior can be reduced by the literacy education in higher education. This solution can be implemented by several methods; (1) mobile financial literacy education, (2) bank products simulations, (3) developing curriculum design by adopting the financial literacy, (4) the technical assistance to the education institution, (5) thematic community service program, (6) providing OJK outlets in higher education. Through financial literacy education in higher education, the wasteful behavior can be reduced and the students’ understanding about financial literacy is advanced.